Modeling Parental Burnout Based on Perceived Social Support with the Mediating Role of Self-Compassion in Parents of Students with Specific Learning Behavioral Disorder - Einali, Zeinab; Jafarian Yasar, Hamid; Pirani, Zabih (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The present study aimed to model parental burnout based on perceived social support with the mediating role of self-compassion in parents of students with specific learning behavioral disorder.Methods and Materials: The study was applied in nature, and its methodology was descriptive-correlational based on structural equation modeling. The statistical population included all parents with one or more children diagnosed with specific learning behavioral disorder in Hamadan Province who visited learning disorder treatment centers during the 2021–2022 academic year. A total of 305 individuals were selected using convenience sampling. Data were collected using the Parental Burnout Assessment (PBA), the Perceived Social Support Questionnaire by Zimet et al. (1988), and the Self-Compassion Scale-Short Form (SCS-SF) by Neff. Data analysis was conducted through structural equation modeling using AMOS software.Findings: The results indicated that self-compassion mediates the positive relationship between perceived social support and parental burnout.Conclusion: It can be concluded that self-compassion helps parents avoid perceiving themselves as isolated from others or viewing their problems as more significant than those of others, which, in turn, prevents burnout.